2022
DOI: 10.20525/ijrbs.v11i6.1964
|View full text |Cite
|
Sign up to set email alerts
|

The common characteristics of employment status during the Covid-19 Lockdown

Abstract: The National Development Plan (NDP) of South Africa identifies the main ills that must be dealt with by 2030. These are poverty and inequality. The NDP also clearly points out the need to deal with unemployment. These build into the sustainable development goals with 2030 as the target year for achievement. Both the NDP for South Africa and the SDGs at the global level had these targets set way before the 2019 coronavirus hit. Now given the disruption that this pandemic caused, the trends and possibility of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A study conducted by Siddiqa (2021) on the determinants of unemployment in selected 10 developing countries found that unemployment has a negative relationship with economic growth, inflation, and expenditure on education while it had a positive relationship with population growth, in essence this means an improvement in economic growth will go a long way in curbing the negative consequences of unemployment. Furthermore, studies have also shown that unemployment has a very strong youth bias (Mncayi & Dunga 2016, Dunga 2022. Young people are more likely to lose their jobs than the adult population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted by Siddiqa (2021) on the determinants of unemployment in selected 10 developing countries found that unemployment has a negative relationship with economic growth, inflation, and expenditure on education while it had a positive relationship with population growth, in essence this means an improvement in economic growth will go a long way in curbing the negative consequences of unemployment. Furthermore, studies have also shown that unemployment has a very strong youth bias (Mncayi & Dunga 2016, Dunga 2022. Young people are more likely to lose their jobs than the adult population.…”
Section: Literature Reviewmentioning
confidence: 99%